Management of Royalties for Copyright Local Songs and Music: Implementation and Urgency - Yohanes Usfunan; Jimmy Z. Usfunan; Made Aditya Pramana Putra; Ni Wayan Ella Apryani; Leonito Ribeiro (Lex Scientia Law Review, 2025)
This study is driven by the ongoing challenges in royalty management arrangements for copyrighted songs and regional music, despite the existence of relevant regulations. In this context, the issues originated from the public’s limited understanding of copyright infringement, as well as a lack of awareness regarding the rights of songwriters and regional musicians to receive royalties. In some cases, songwriters and musicians resort to informal or underhanded agreements concerning the use of respective songs. Therefore, this study aims to thoroughly examine the royalty management policies for copyrighted songs and local music in Indonesia, to emphasize the urgency of royalty management in the sector, and to explore the issue from a human rights perspective. In order to achieve the stated objectives, a normative study approach was utilized, adopting both a legislative approach and legal concept analysis. The obtained results showed that royalty management policies for copyrighted songs and regional music were regulated under Government Regulation 56/2021, implemented through National Collective Management Institution (Lembaga Manajemen Kolektif Nasional/LMKN) and Collective Management Institution (LMK). The management of royalties is very important, as it provides benefits not only to creators and related stakeholders but also contributes to the development of music in society. Furthermore, royalty management, as an expression of economic rights, was recognized as part of ECOSOB human rights.